Numerical investigation of the ability of eddy current testing to size surface breaking cracks. Issue 1 (2nd January 2017) - Yusa, Noritaka; Hashizume, Hidetoshi
Abstract: This study attempts to estimate the limitations of eddy current testing for evaluating the depth of a crack with the aid of numerical simulations. Three-dimensional finite element simulations were conducted to obtain eddy current signals resulting from a crack in a plate made of Ni-based alloy. The simulations modelled the crack as a sufficiently long rectangular region with a constant width and depth. A uniform conductivity was given inside the modelled crack because actual cracks do not always behave as electrically insulating walls. The conductivity of the modelled crack was chosen on the basis of a recent study reporting how real cracks can be modelled from the viewpoint of electromagnetic non-destructive evaluation. This study considered three conventional eddy current probes: a pancake probe, a vertical pancake probe and a plus point probe. The results of the simulations reveal that lower frequency does not always enhance the evaluation of a deeper crack if the crack is conductive; moreover, the maximum depth of a stress corrosion crack that conventional eddy current testing can evaluate quantitatively should be limited to a few mm at most. In contrast, the simulations also demonstrate that the ability of eddy current testing to size a fatigue crack would not differ significantly from that to size an artificial slit.